Critical role of synovial tissue–resident macrophage niche in joint homeostasis and suppression of chronic inflammation - Huang, Qi-Quan (Sci Adv, 2021)
Little is known about the mechanisms regulating the transition of circulating monocytes into pro- or anti-inflammatory macrophages in chronic inflammation. Here, we took advantage of our novel mouse model of rheumatoid arthritis, in which Flip is deleted under the control of a CD11c promoter (HUPO mice). During synovial tissue homeostasis, both monocyte-derived F4/80(int) and self-renewing F4/80(hi) tissue–resident, macrophage populations were identified. However, in HUPO mice, decreased synovial tissue–resident macrophages preceded chronic arthritis, opened a niche permitting the influx of activated monocytes, with impaired ability to differentiate into F4/80(hi) tissue–resident macrophages. In contrast, Flip-replete monocytes entered the vacated niche and differentiated into tissue-resident macrophages, which suppressed arthritis. Genes important in macrophage tissue residency were reduced in HUPO F4/80(hi) macrophages and in leukocyte-rich rheumatoid arthritis synovial tissue monocytes. Our observations demonstrate that the macrophage tissue–resident niche is necessary for suppression of chronic inflammation and may contribute to the pathogenesis of rheumatoid arthritis.